2007
DOI: 10.1002/prep.200700030
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Pressure Thresholds from Three Sources

Abstract: Pressure thresholds are minimum pressures needed to start explosive initiation that ends in detonation. We obtain pressure thresholds from three sources. Run‐to‐detonation times are the poorest source but the fitting of a function gives rough results. Flyer‐induced initiation gives the best results because the initial conditions are the best known. However, very thick flyers are needed to give the lowest, asymptotic pressure thresholds used in modern models and this kind of data is rarely available. Gap test d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Indentation then drops rapidly and less reproducible responses are observed in the interval 1.1-1.2 g/cm 3 . This is probably explained by a decrease in shock sensitivity of pressed UHP due to pressurisation, which decreases the density of potential hotspots that play a key role in detonation propagation in heterogeneous explosives [15,27].…”
Section: Validated Set-upmentioning
confidence: 99%
“…Indentation then drops rapidly and less reproducible responses are observed in the interval 1.1-1.2 g/cm 3 . This is probably explained by a decrease in shock sensitivity of pressed UHP due to pressurisation, which decreases the density of potential hotspots that play a key role in detonation propagation in heterogeneous explosives [15,27].…”
Section: Validated Set-upmentioning
confidence: 99%
“…The initiation and subsequent transition to sustained detonation of an explosive is believed to be associated with the adiabatic compression of voids or "hot spots" in the explosive [4,5]. It has been shown that for non-ideal explosives the critical energy or pressure of initiation is a function of the density [6]. This being the case, the quality of explosive crystals is expected to impact their initiability.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the choice of only a single parameter s , rather than multiple, is already a grossly simplifying assumption; see, e. g ., higher‐order rate improvements to CREST to address just such a concern. Perhaps more importantly, there is empirical evidence to suggest that it may be better to use some combination of pmax and the duration of the high‐pressure spike rather than pmax alone. The need for such improvements is not surprising and indeed can be argued on very simple physical grounds.…”
Section: Model As Tested: Salinas 10mentioning
confidence: 99%